PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN PADA HOTEL NEW RESTY MENARA PEKANBARU - Dalimunthe, Rahmad; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine how much influence service quality and corporate image towards customer satisfaction at new resty menara pekanbaru hotel. The sample of the present researchers was taken as many as 100 respondents and the technique used was incidental sampling. The data in this study used the survey method through a questionnaire filled out by Customer. Data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS18 program.The results of this study indicate that the service quality variable has a positive and significant influence on Customer Satisfaction in the New Resty Hotel, Pekanbaru Tower. And the corporate image variable has a positive and significant influence on Customer Satisfaction in the New Resty Hotel, Pekanbaru Tower. Then simultaneously service quality and corporate image have a positive and significant influence on Customer Satisfaction at the New Resty Hotel, Pekanbaru Tower. For further research it is recommended to increase the number of respondents in the sample calculation. Keywords: Service Quality, Corporate Image. And Customer Satisfaction